Obtaining flour from acerola processing residue and evaluating bioactive and nutritive compounds (Research, Society and Development, 2021)
Acerola is a fruit of great nutritional value recognized for its high vitamin C content, and has varied applicability in the food industry. Its processing generates a considerable amount of waste, and there is a lack of information on the composition and use of this material. This study aimed to produce a flour from the residue of acerola pulping, carry out the physicochemical characterization and analysis of bioactive compounds, aiming at a possible use for food purposes. The flour, consisting of seed and peel of the fruit was shown to be a nutritionally rich by-product, containing 9.12% protein, 3.40% lipids, 1.76% ash, 6.64% moisture and 79.07% carbohydrates, pH of 3.23 and titratable acidity of 3.30 g citric acid/100g. As for bioactive compounds, the flour showed high levels of vitamin C (764.40 mg/100 g), carotenoids (23.93 µg/g), total phenolic compounds (28.46 mg AGE/100 g), antioxidant activity by radical DPPH (EC50 113.40 g of flour/g DPPH) and ABTS (193.90 μmol/g of flour). The flour developed presented itself as an alternative to be used for food purposes, with good conservation due to its low water content, in addition to contributing to the reduction of agro-industrial residues.